Hebert A. Simon y la economía organizacional - Estrada Gallego, Fernando (Sociedad y Economía, 2006)
This article develops an evaluation of the contributions of Herbert A. Simon to the theory of organizations providing special emphasis to the criterion of limited rationality (bounded rationality). The critic of Simon to the orthodox version of organizacional bureaucracy is interpreted and his analysis is extended towards institutional economy. One of the main achievements of Herbert Simon in organizacional theory consists of analitically valuing the psychology of individual and collective behavior, opening in this way the space for later research of D. Kahneman and T. Schelling.